2017
DOI: 10.1177/1468087417710583
|View full text |Cite
|
Sign up to set email alerts
|

Particulate emissions from a highly boosted gasoline direct injection engine

Abstract: Downsized, highly boosted, gasoline direct injection engines are becoming the preferred gasoline engine technology to ensure that increasingly stringent fuel economy and emissions legislation are met. The Ultraboost project engine is a 2.0-L in-line four-cylinder prototype engine, designed to have the same performance as a 5.0-L V8 naturally aspirated engine but with reduced fuel consumption. It is important to examine particle number emissions from such extremely highly boosted engines to ensure that they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…EGR, if it is not cooled, will have a similar effect for similar reasons, however cooled external EGR is becoming more common in GDI engines today, and the effect of EGR on inlet air temperature is not present with this type of EGR. Therefore the effect of cooled, external EGR can be to increase particulate emissions as EGR reduces exhaust temperatures, reducing post-flame oxidation, other studies have found a modest decrease with EGR, attributed to lower combustion temperatures, and a reduction in mixture enrichment at high load [94][95][96].…”
Section: Egr and Inlet Air Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…EGR, if it is not cooled, will have a similar effect for similar reasons, however cooled external EGR is becoming more common in GDI engines today, and the effect of EGR on inlet air temperature is not present with this type of EGR. Therefore the effect of cooled, external EGR can be to increase particulate emissions as EGR reduces exhaust temperatures, reducing post-flame oxidation, other studies have found a modest decrease with EGR, attributed to lower combustion temperatures, and a reduction in mixture enrichment at high load [94][95][96].…”
Section: Egr and Inlet Air Conditionsmentioning
confidence: 99%
“…Such engines will not have inherent differences in their PM emissions, and such emissions have not been significantly studied in detail at the time of writing. The studies that have been undertaken report that there is a bias towards smaller particle sizes in the PN emissions from these engines (possibly due to their higher in-cylinder pressures), and that certain parameters important in boosted engines, such as exhaust back pressure, serve to reduce PN emissions [96,113,114].…”
Section: Boosted Enginesmentioning
confidence: 99%
“…In addition, all gases and particularly those retained inside the cylinder at IVC are considered ideal. Thus, the system can be expressed through Equation (12). Instantaneous volume at IVC (V IVC ) has been indirectly calculated through the crank slider with pin offset equation, using nominal crank position (angle).…”
Section: = (6)mentioning
confidence: 99%
“…Nevertheless the size distribution in gasoline direct injection (GDI) engines may be wide due to higher concentration of volatiles in the fuel. Proportion of sub-23nm particulates reported in the literature is up to 40% 6,7 .…”
Section: Introductionmentioning
confidence: 99%